Are predictive models useful in clinical medicine? - Cerfolio, Robert J. (Journal of Thoracic Disease, 2018)
The authors have submitted a very interesting paper that is a predictive model—meaning there are no new patients in this study. Rather the authors have search the literature to find all of the best articles that show the accuracy of EUS and then they used the National Cancer Database to show estimates of survival of subgroups of patients. Armed with these heterogonous data sets and many assumptions they construct a predictive model for patients with clinical T2N0M0 esophageal cancer.